Malignant hemangiopericytoma of pituitary fossa - Das Prasenjit; Haresh Kunhi; Suri Vaishali; Sharma Mehar; Sharma Bhawani; Sarkar Chitra (Wolters Kluwer Medknow Publications, 2010)
Intracranial hemangiopericytomas are rare tumors with aggressive behavior. Other than the meninges, this lesion has rarely been reported in periventricular and sellar region. We report a case of malignant hemangiopericytoma in sellar region in a 47-year-old male who presented with history of sudden onset of bilateral visual disturbances. To best of our knowledge, this is the second case report of malignant hemangiopericytoma in this location. As this intracranial lesion shows aggressive behavior, in the form of recurrence or extracranial metastasis in comparison to its extracranial counterparts, diagnosis should be made cautiously.